Machines and how they work - Weiss, Harvey (New York : Crowell, 1983)
An introduction to six simple machines--the lever, the inclined plane, the screw, the wheel and axle, the wedge, and the pulley--and their use in more complex machines such as derricks, bulldozers, and metal lathes.
Booklist.
5.2
5.2
5-8.
5-8
Keywords: Gearing -- Juvenile literature; Levers -- Juvenile literature; Pulleys -- Juvenile literature; Simple machines -- Juvenile literature; Simple machines; Machinery